Influence of particle size and fluorination ratio of CFx precursor compounds on the electrochemical performance of C–FeF2 nanocomposites for reversible lithium storage - Breitung, Ben; Reddy, M. Anji; Chakravadhanula, Venkata Sai Kiran; Engel, Michael; Kübel, Christian; Powell, Annie K.; Hahn, Horst; Fichtner, Maximilian (Beilstein Journal of Nanotechnology, 2013)
Systematical studies of the electrochemical performance of CFx-derived carbon–FeF2 nanocomposites for reversible lithium storage are presented. The conversion cathode materials were synthesized by a simple one-pot synthesis, which enables a reactive intercalation of nanoscale Fe particles in a CFx matrix, and the reaction of these components to an electrically conductive C–FeF2 compound. The pretreatment and the structure of the utilized CFx precursors play a crucial role in the synthesis and influence the electrochemical behavior of the conversion cathode material. The particle size of the CFx precursor particles was varied by ball milling as well as by choosing different C/F ratios. The investigations led to optimized C–FeF2 conversion cathode materials that showed specific capacities of 436 mAh/g at 40 °C after 25 cycles. The composites were characterized by Raman spectroscopy, X-Ray diffraction measurements, electron energy loss spectroscopy and TEM measurements. The electrochemical performances of the materials were tested by galvanostatic measurements.
Keywords: conducting carbon; conversion material; enregy-related; graphite fluoride; lithium battery; iron fluoride